Chinese Investments in Africa : Development Assistance or Predation ? - Vedie, Henri-Louis (DEMO, 2016)
For many observers, chinese activity in Africa is the mark of predator. Topic of this paper is, from recents statistics, to answer at one simple question. Is chinese activity in Africa a new form of colonialism ? Detailed analyses of chinese investments, between 2005-2013, shows that all investments represented only 3% of the total of chinese investment in the world. And during this period, the chinese target has been always the same, 70% of this investments being only in three sectors : petrol, mining and transport. For 2014, we have to remind a new behaviour of the chinese country, allowing to share better advantages and disadvantages for the two countries, banishing perhaps definitely idea of a predatory China.(original abstract)
Keywords: Investment; Long-term investments; International investment; Transport; Industrial commodities